ANALISIS PRAKTEK INCOME SMOOTHING PADA PERUSAHAAN PENYEDIA JASA TELEKOMUNIKASI DI INDONESIA - Cholid, Mohammad Ilham; Putra, Mochamad Rohiki Santoso; Febrianti, Sagita; Fadila, Husnul (Jurnal Profiet, 2024)
Research on income smoothing analysis and the factors that influence it in companies providing telecommunications services which are based on conflicts of interest are explained by agency theory and the existence of opportunistic actions is explained by positive accounting theory. The variables used in this research are profitability which is calculated by Return on Assets, cash holding which is calculated by the ratio of cash and cash equivalents to total assets, and financial leverage which is calculated by the Debt to Equity ratio. The aim of this research is to analyze the influence of these variables on the role of profit. This research uses quantitative descriptive methods. The data used is secondary data in the form of financial reports of telecommunications service provider companies obtained from the Indonesia Stock Exchange for the 2019-2023 period. Three hypotheses were formulated and tested using Logistic Regression Analysis. The research results show that profitability has a significant effect on income smoothing. However, holding capital and financial leverage do not have a significant effect on income smoothing. Keywords: Income Smoothing, Profitability, Cash Holding, Financial Leverage